2020
DOI: 10.1101/2020.04.24.20078568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laboratory Findings of COVID-19 Infection are Conflicting in Different Age Groups and Pregnant Women: A Literature Review

Abstract: Coronavirus disease 2019 , a new type and rapidly spread viral pneumonia, is now producing an outbreak of pandemic proportions. The clinical features and laboratory results of different age groups are different due to the general susceptibility of the disease. The laboratory findings of COVID-19 in pregnant women are also conflicting. Para-clinical investigations including laboratory tests and radiologic findings play an important role in early diagnosis and treatment monitoring of severe acute respiratory syn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
(50 reference statements)
2
22
2
2
Order By: Relevance
“…It may be due to the direct contribution of the virus or redistribution of WBC via chemotaxis or apoptosis [ 16 , 41 , 60 ]. Compared to non-severe ones, severe cases are older and have comorbidity diseases [ [61] , [62] , [63] ], making them more susceptible to endothelial dysfunction and its associated lymphopenia. The fact that the present study showed elevated leukocyte levels in severe compared to non-severe patients across 42 studies is a novel and controversial finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to the direct contribution of the virus or redistribution of WBC via chemotaxis or apoptosis [ 16 , 41 , 60 ]. Compared to non-severe ones, severe cases are older and have comorbidity diseases [ [61] , [62] , [63] ], making them more susceptible to endothelial dysfunction and its associated lymphopenia. The fact that the present study showed elevated leukocyte levels in severe compared to non-severe patients across 42 studies is a novel and controversial finding.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes might be the poor description of the analytical performance features of the methods applied among the included studies. Furthermore, aging as a condition related to the inflammation was the basis of the previous studies [ 62 , 71 ], showing that severe patients were older than non-severe ones. Since the proinflammatory response is believed to initiate SARS-CoV-2 infection, it is logically possible that the aged cases have an overwhelming inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the clinical symptoms and pulmonary computed tomography (CT) findings, a large number of COVID-19 confirmed patients showed laboratory fluctuations including complete blood count (CBC) variables, cardiac and coagulation parameters, renal and liver function tests, and inflammation-related factors [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the clinical symptoms and pulmonary computed tomography (CT) findings, a large number of COVID-19 confirmed patients showed laboratory fluctuations including complete blood count (CBC) variables, cardiac and coagulation parameters, renal and liver function tests, and inflammation-related factors (6,7).…”
Section: Introductionmentioning
confidence: 99%